Preliminary investigation on feeding habits and gonad maturation in North Adriatic wild turbot (Scophthalmus maximus L.) - P. Melotti; A. Dees; O. Mordenti; A. Roncarati (Italian Journal of Animal Science, 2011)
The European aquaculture turbot production in 1999 was 4093 t of which approximately 2850 t from Spain. France (858 t), Portugal (378 t) and Ireland (8 t) are the other main turbot producing countries in Europe (FAO, 2001). Several studies have been carried out detailing the high potential of turbot but they report operative conditions of the north of Europe because this species requires temperatures around 16 °C for optimal growth (Nijhof, 1994). Due to its high market value, turbot is profitable using technologically advanced production systems...